Antifungal activity of extracts and prenylated coumarins isolated from baccharis darwinii hook & arn. (asteraceae) - Kurdelas, Rita Rosa (2010)
The petroleum ether extract of Baccharis darwinii showed activity against Cryptococcus neoformans and dermatophytes. Bioactivity-guided fractionation of Baccharis darwinii has resulted in the isolation of three coumarins: 5'-hydroxy aurapten (anisocoumarin H, 1), aurapten (7-geranyloxycoumarin, 2) and 5'-oxoaurapten (diversinin, 3). The structures of these compounds were characterized by spectroscopic methods. These compounds were evaluated for their antimicrobial activity against a panel of each, bacteria and fungi. Compound 3 showed the best activities against Microsporum gypseum, Trichophyton rubrum and Trichophyton mentagrophytes with MICs = 15.6 μg/mL, followed by compound 1 whose MICs against the same fungi were 62.5 μg/mL. In addition they showed fungicidal rather than fungistatic activity. Both compounds showed moderate activity (MICs = 125 μg/mL) against Cryptococcus neoformans. This is the first report of the presence of compound 1 in B. darwinii.